1874 Ky. Acts 332, An Act to Revise and Amend the Charter of the City of Newport, § 6. - (:unkn) unknown (General Publisher, 1874)
To prohibit the manufacture of gunpowder or other explosive, dangerous, or noxious compounds or substances in said city, and to regulate their sale and storage by license.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER